A high-strength anti-infection titanium alloy and its preparation method and application

By adding Cu elements to medical Ti6Al4V alloy and performing cold drawing deformation and low-temperature aging treatment, nano-scale Ti2Cu precipitation phase is formed, which solves the shortcomings of medical titanium alloy in terms of high strength and antibacterial properties, and achieves high strength and excellent antibacterial properties titanium alloy materials.

CN116377281BActive Publication Date: 2025-04-29FOSHAN HOSPITAL OF TCM +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310202005.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-04-29
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

Existing medical titanium alloys are prone to bacterial infection during use, and their mechanical properties are low in environments with high strength performance requirements, making it difficult to meet clinical needs.

Method used

Add an appropriate amount of Cu elements to the medical Ti6Al4V alloy matrix, and cold-drawing deformation and low-temperature aging treatment are carried out to form a nano-scale Ti2Cu precipitation phase. Through deformation strengthening and second phase precipitation composite strengthening, the mechanical properties of the material and anti-bacterial infection function are improved.

Benefits of technology

It has achieved high strength and excellent antibacterial properties of titanium alloys, with tensile strength up to 1350-1518MPa, hardness up to 420.6-467.6HV, and sterilization rate up to 99.2-99.9%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116377281B_ABST
    Figure CN116377281B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of alloy materials, and specifically discloses a high-strength anti-infection titanium alloy and its preparation method and application. The chemical composition of the titanium alloy, by mass percentage, is Al: 5.5 - 6.5%, V: 3.5 - 4.5%, Cu: 4.5 - 5.5%; the balance is Ti; the titanium alloy includes cold drawing deformation and low-temperature aging treatment. By adding a certain amount of copper element to the Ti6Al4V alloy matrix, controlling the chemical composition of each element, and performing cold drawing deformation and low-temperature aging treatment on it, cold deformation defects are introduced into the material matrix through cold drawing deformation, and then low-temperature aging treatment is adopted, so that the precipitated phase Ti2Cu can be evenly precipitated at the deformation band, and the precipitated phase precipitated by this low-temperature aging has the characteristic of small size, which can not only greatly improve the mechanical properties of the material, but also further endow the material with excellent antibacterial properties, achieving a tensile strength of 1350 - 1518 MPa, a hardness value of 420.6 - 467.6 HV, and a sterilization rate of 99.2 - 99.9%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials, and in particular to the technical field of medical titanium alloy materials, and specifically relates to a high-strength anti-infection titanium alloy and a preparation method and application thereof. Background Art

[0002] Medical titanium alloys are currently a type of medical metal material widely used in clinical practice due to their non-magnetic, non-toxic, excellent biocompatibility, good wear and corrosion resistance and comprehensive mechanical properties. They have been widely used in artificial joints, fracture internal fixation devices, spinal orthopedic internal fixation systems, dental repairs and many other implant devices. Ti6Al4V (TC4) titanium alloy is the first generation of medical titanium alloys widely used in the manufacture of implant devices. Its main alloying elements are aluminum (Al) and vanadium (V). Compared with pure titanium, Ti6Al4V is an α+β type titanium alloy with excellent mechanical properties and good processing properties. It has a long history of clinical application as a surgical repair material such as bone pins, bone plates, and intramedullary nails.

[0003] However, during the use of implantable medical metals, there is a problem of bacterial infection at the surgical site, and local bacterial infection caused by implanted medical devices is one of the most common complications at present. Postoperative infection not only leads to poor functional recovery of patients, but also prolongs the patient's hospitalization time. Patients also need to undergo another surgery to remove the implanted medical device and remove the lesion, which brings heavy economic burden and mental pressure to patients. Statistics from the World Health Organization show that more than 14 million people in the world experience the risk of hospital infection every day, of which 60% of bacterial infections are related to the medical devices used. According to statistics, in the United States, where the medical level is well developed, the annual incidence of orthopedic implant-related infection has reached about 4.3%. At this stage, the increasingly serious problem of bacterial infection not only brings great physical and mental pain and heavy economic burden to patients, but also has different degrees of negative impact on hospitals and society.

[0004] In addition to the problem of bacterial infection caused by implantable medical devices, the clinical demand for high-strength medical metals is becoming more urgent. Although medical titanium alloys have excellent comprehensive performance, their application is greatly limited in some environments that require high-strength performance. At present, medical titanium alloys mainly improve their strength through deformation strengthening and second-phase strengthening, but after strengthening, the mechanical properties of medical titanium alloys are still low, so it is necessary to introduce new strengthening methods to obtain high-strength medical titanium alloys.

[0005] Therefore, there is an urgent need to develop a medical titanium alloy that can improve its mechanical properties while maintaining good antibacterial properties. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a high-strength anti-infection titanium alloy and its preparation method and application, by adding an appropriate amount of Cu element with strong bactericidal effect to the medical Ti6Al4V alloy matrix, and then subjecting the cold-drawn deformed copper-containing titanium alloy to low-temperature aging treatment, so that a fine and uniform nano-scale Ti2Cu precipitation phase is precipitated in the deformation zone of the titanium alloy matrix, and the composite strengthening of deformation strengthening and second phase precipitation is utilized to give the Ti6Al4V medical titanium alloy excellent mechanical properties and anti-bacterial infection function.

[0007] In order to overcome the above technical problems, the first aspect of the present invention provides a titanium alloy, the chemical composition of which is Al: 5.5-6.5%, V: 3.5-4.5%, Cu: 4.5-5.5% by mass percentage; the balance is Ti;

[0008] The process of preparing the titanium alloy includes cold drawing deformation and low temperature aging treatment.

[0009] Specifically, the present invention adds an appropriate amount of Cu element with strong bactericidal effect to the Ti6Al4V alloy matrix, and performs cold drawing deformation and low-temperature aging treatment on it to form a composite strengthening method of strengthening and second phase precipitation, thereby giving the material excellent mechanical properties and anti-infection properties. For the copper-containing titanium alloy in the solid solution state, the precipitation nose temperature of the Ti2Cu precipitation phase is generally about 750°C, and the nose precipitation time is about 30min. At this time, the size of the precipitated precipitate phase is relatively large, mainly precipitated at the α and β phase boundaries, and the size is generally about 50nm, which has limited improvement on strength. The present invention applies cold drawing deformation to the copper-containing titanium alloy, and a large number of deformation bands are generated in the matrix. The defect density in these deformation bands is high, the atomic arrangement is chaotic, and the atoms are easy to diffuse along the crystal defects. There are a large number of nucleation sites, and a large amount of deformation energy is stored in the deformation band. Therefore, after aging at a lower temperature, the precipitate phase can be uniformly precipitated at the deformation band. Different from Ti2Cu directly precipitated from the solid solution (precipitation at the phase boundary), the precipitated phase precipitated by low-temperature aging (precipitation within the phase) is smaller in size (<5nm), which can greatly improve the mechanical properties of the material and further give the material excellent antibacterial properties.

[0010] Preferably, the chemical composition of the titanium alloy, by mass percentage, is Al: 5.6-6.2%, V: 3.7-4.3%, Cu: 4.5-5.4%; the remainder is Ti.

[0011] As a further improvement of the above solution, the cross-sectional deformation of the cold drawing deformation is not less than 30%.

[0012] Specifically, the effect of this large deformation is to produce defects such as deformation bands in the material. The energy density at the deformation band is high and unstable. During the low-temperature aging treatment, the Ti2Cu phase is precipitated, and the copper-rich phase of the Ti2Cu phase produced by low-temperature aging is smaller. Through the nano-scale copper-rich phase (precipitation strengthening) and cold deformation strengthening (deformation strengthening), its strength and antibacterial properties can be more effectively improved. If the cold deformation is small, the deformation band inside the material will decrease, and the corresponding volume fraction of the precipitated Ti2Cu phase will also decrease. The second phase strengthening and deformation strengthening are not sufficient, resulting in low strength of the material.

[0013] As a further improvement of the above solution, the temperature of the low-temperature aging treatment is 550-650°C.

[0014] Specifically, low-temperature aging treatment at 550-650°C can make fine dispersed Ti2Cu precipitate evenly in the deformation zone. In addition, the aging temperature should not be too low, and the aging time should not be too short. From a kinetic point of view, it will be unfavorable for the precipitation of the intermediate phase. If the aging temperature is too high and the aging time is too long, the precipitated phase will be coarse, affecting the mechanical and corrosion resistance of the material. By introducing the deformation zone through cold deformation, the uniform precipitation of fine Ti2Cu in the deformation zone is regulated, so that the copper-containing titanium alloy has high strength and excellent antibacterial properties.

[0015] A second aspect of the present invention provides a method for preparing a titanium alloy, wherein the method is used to prepare the titanium alloy according to the first aspect of the present invention, and comprises the following steps:

[0016] (1) Smelting titanium alloy raw materials, hot forging and hot rolling to obtain hot-rolled wire rods;

[0017] (2) subjecting the hot-rolled wire rod to annealing heat treatment and pickling to obtain annealed hot-rolled wire rod;

[0018] (3) The annealed hot-rolled wire rod is subjected to cold drawing deformation and low-temperature aging treatment in succession to obtain the titanium alloy.

[0019] Specifically, the commonly used heat treatment method for copper-containing titanium alloys is solid solution + aging treatment, wherein: the role of aging treatment is to precipitate copper-rich phases to ensure the antibacterial properties of the material. The present invention performs low-temperature aging treatment after cold drawing deformation, which can cause the copper-rich phase (produced by annealing heat treatment) decomposed by deformation to precipitate again, which is beneficial to simultaneously improve the mechanical properties and antibacterial properties of the material.

[0020] Preferably, in step (1), the hot forging temperature is 950-1250°C, the holding time is 1-2 hours, and the final forging temperature is not less than 900°C.

[0021] Preferably, in step (1), the hot rolling temperature is 800-850°C, the holding time is 1-2 hours, and the final rolling temperature is not less than 750°C.

[0022] Specifically, in addition to controlling the hot forging temperature and the hot rolling temperature, the present invention further controls the final forging temperature and the final rolling temperature, which can effectively prevent defects (cracks, etc.) in the material due to too low temperature during the hot working process.

[0023] Preferably, in step (2), the annealing heat treatment is performed at a temperature of 750-800° C. and a holding time of 1-2 hours.

[0024] Preferably, in step (3), the cross-sectional deformation amount of the cold-drawing deformation is 30-40%. Further preferably, in step (3), the cross-sectional deformation amount of the cold-drawing deformation is 34-38%.

[0025] Preferably, in step (3), the temperature of the low-temperature aging treatment is 550-640° C., and the insulation time is 1-2 hours.

[0026] The third aspect of the present invention provides the use of the titanium alloy described in the first aspect of the present invention in medical materials.

[0027] Preferably, the medical material comprises implantable medical titanium alloy material.

[0028] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0029] (1) The present invention adds a certain amount of copper element to the Ti6Al4V alloy matrix, controls the chemical composition of each element, and simultaneously performs cold drawing deformation and low-temperature aging treatment on the Ti6Al4V alloy. Cold deformation defects (deformation bands) are introduced into the material matrix by cold drawing deformation, and then low-temperature aging treatment is performed, so that the precipitated phase Ti2Cu can be uniformly precipitated at the deformation band. The precipitated phase precipitated by low-temperature aging has the characteristic of small size, which can not only greatly improve the mechanical properties of the material, but also further give the material excellent antibacterial properties.

[0030] (2) The titanium alloy prepared by the present invention has a tensile strength of 1350-1518 MPa and a hardness of 420.6-467.6 HV; at the same time, it has excellent antibacterial properties, and the bactericidal rate can reach 99.2-99.9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 TEM image of the titanium alloy prepared in Example 4;

[0032] Figure 2 is the SAD diffraction pattern of the titanium alloy prepared in Example 4;

[0033] Figure 3 This is a comparison chart of the mechanical properties of the titanium alloy before and after low-temperature aging treatment during the preparation process of Example 4. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0035] Example 1

[0036] Examples 1-6 and Comparative Examples 1-6

[0037] The chemical compositions of the titanium alloys of Examples 1-6 and Comparative Examples 1-6 are shown in Table 1.

[0038] Table 1: Chemical composition of titanium alloys of Examples 1-6 and Comparative Examples 1-6 (wt.%)

[0039] Material Al V Cu Ti Example 1 5.6 3.8 4.5 margin Example 2 5.8 3.9 4.7 margin Example 3 6.2 4.2 4.9 margin Example 4 5.8 4.3 5.0 margin Example 5 5.7 3.7 5.2 margin Example 6 6.1 3.7 5.4 margin Comparative Example 1 5.8 4.3 5.0 margin Comparative Example 2 5.8 4.3 5.0 margin Comparative Example 3 5.8 4.3 5.0 margin Comparative Example 4 5.8 4.3 5.0 margin Comparative Example 5 5.8 3.9 4.0 margin Comparative Example 6 6.1 4.2 6.0 margin

[0040] The preparation method of the titanium alloy of Examples 1-6 and Comparative Examples 1-6 comprises the following steps:

[0041] (1) According to the chemical composition range shown in Table 1, the titanium alloy was smelted in a vacuum induction furnace, firstly hot forged by keeping the temperature at 1000° C. for 1.5 hours, and then hot rolled by keeping the temperature at 825° C. for 1.5 hours to obtain a hot-rolled wire rod (bar) with a diameter of 4 mm;

[0042] (2) subjecting the hot-rolled wire rod obtained in step (1) to an annealing heat treatment at 700° C. for 1 hour, and then pickling the hot-rolled wire rod to obtain an annealed hot-rolled wire rod;

[0043] (3) The annealed hot-rolled wire rod obtained in step (2) is first subjected to cold drawing deformation, wherein the cross-sectional deformation of the cold drawing deformation is 36%; and then subjected to low-temperature aging treatment to obtain a titanium alloy (wire) with a diameter of 3.2 mm.

[0044] In the preparation methods of the titanium alloys of Examples 1-6 and Comparative Examples 1-6, the temperature and time parameters of low temperature aging are shown in Table 2.

[0045] Table 2: Parameters of low temperature aging treatment of titanium alloys of Examples 1-6 and Comparative Examples 1-6

[0046] Material Low temperature aging temperature (℃) Low temperature aging time (h) Example 1 550 1 Example 2 570 1.5 Example 3 580 1 Example 4 600 2 Example 5 620 1.5 Example 6 640 1.5 Comparative Example 1 700 2 Comparative Example 2 600 2.5 Comparative Example 3 450 2 Comparative Example 4 600 0.5 Comparative Example 5 600 2 Comparative Example 6 600 2

[0047] Performance Testing

[0048] 1. Microstructure

[0049] The titanium alloy sample prepared in Example 4 was subjected to microstructural testing, and the results are as follows: Figure 1-2 As shown by Figure 1-2 It can be seen that after cold drawing deformation + low-temperature aging treatment, a large amount of nano-scale Ti2Cu with a diameter of less than 5nm is precipitated in the deformation band of the material substrate.

[0050] 2. Mechanical properties

[0051] According to relevant standards such as GB / T 228-2010 Tensile test of metallic materials Part 1: Room temperature test method and GB / T 4342-1991 Metal micro-Vickers hardness test method, the room temperature tensile properties and microhardness values ​​of the metals with the components shown in Table 1 (Examples 1-6 and Comparative Examples 1-6) were quantitatively tested, and the test results are shown in Table 3.

[0052] Figure 3 This is a comparison of the mechanical properties of the titanium alloy before and after low-temperature aging treatment in the preparation process of Example 4. In the figure, the horizontal axis Engineering strain represents the engineering strain; the vertical axis Engineering stress represents the engineering stress. Figure 3 It can be seen that compared with single cold drawing deformation, the mechanical properties of the material after cold drawing deformation + low-temperature aging treatment have been greatly improved.

[0053] 3. Antibacterial properties

[0054] According to the relevant standards such as "JIS Z 2801-2000 "Antibacterial processed products - Antibacterial test methods and antibacterial effects", GB / T2591-2003 "Antibacterial plastics antibacterial performance test methods and antibacterial effects", the sterilization rate of the metal components (Examples 1-6 and Comparative Examples 1-6) shown in Table 1 on common infectious bacteria (such as Escherichia coli E.coli, Staphylococcus aureus S.aureus) was quantitatively tested. The calculation formula of the sterilization rate is: Sterilization rate (%) = [(number of viable bacteria in the control sample - number of viable bacteria in the anti-infective medical titanium alloy) / number of viable bacteria in the control sample] × 100%, the number of viable bacteria in the control sample is the number of viable bacteria after bacterial culture on the ordinary Ti6Al4V titanium alloy sample, and the number of viable bacteria in the anti-infective medical titanium alloy refers to the number of viable bacteria after bacterial culture on the anti-infective medical titanium alloy. The test results are shown in Table 3.

[0055] Table 3: Comparison of mechanical properties and antibacterial properties of titanium alloys of Examples 1-6 and Comparative Examples 1-6

[0056]

[0057] From the results in Table 3, it can be seen that the titanium alloys prepared in Examples 1-6 of the present invention all exhibit high-strength mechanical properties and also have excellent antibacterial properties, wherein: the tensile strength can reach 1350-1518MPa, the hardness value can reach 420.6-467.6HV, and the sterilization rate can reach 99.2-99.9%. That is, the titanium alloy prepared in the present invention can have both excellent mechanical properties and antibacterial properties as a result of the combined effect of specific chemical composition and aging treatment process.

[0058] The only difference between Comparative Example 1-2 and Example 4 is that the low temperature aging temperature is higher or the aging time is longer. As shown in Table 3, under the condition of the same copper content, if the aging temperature is too high or the aging time is too long, the Ti2Cu phase in the cold-deformed titanium alloy matrix and the grain boundary will grow abnormally, and the precipitation phase will be precipitated at the phase boundary. The presence of such coarse precipitation phase causes the mechanical properties of the material to be significantly reduced.

[0059] The difference between Comparative Examples 3-4 and Example 4 is that the low-temperature aging temperature is lower or the aging time is shorter. As shown in Table 3, when the copper content is the same, if the aging temperature is too low or the aging time is too short, sufficient Ti2Cu phase cannot be precipitated in the cold-deformed copper-containing titanium alloy matrix, and the performance of the material is close to that of the cold-deformed state, and it cannot have high strength and antibacterial properties.

[0060] Therefore, the low-temperature aging treatment after cold drawing deformation in the present invention has an important influence on the antibacterial property and mechanical properties of titanium alloy.

[0061] The only difference between Comparative Example 5 and Example 4 is that the copper content is lower. As shown in Table 3, under the same low-temperature aging temperature and aging time, when the copper addition amount is too low, the supersaturation of copper in the matrix is ​​too low, resulting in the material being unable to precipitate enough Ti2Cu phase. Therefore, the mechanical properties and antibacterial rate of Comparative Example 5 are inferior to those of Example 4.

[0062] The only difference between Comparative Example 6 and Example 4 is that the copper content is higher. As shown in Table 3, under the same low-temperature aging temperature and aging time, when the copper addition amount is too high, although the material has excellent antibacterial properties, it is also easy to cause abnormal growth of the Ti2Cu phase and reduce its mechanical properties.

[0063] Therefore, the copper content should be controlled within a suitable range, and the appropriate low-temperature aging heat treatment system should be adjusted so that the cold-deformed copper-containing titanium alloy can have both excellent mechanical properties and antibacterial properties.

[0064] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. A titanium alloy, characterized in that: Its chemical composition, by mass percentage, is Al: 5.5-6.5%, V: 3.5-4.5%, Cu: 4.5-5.5%; the balance is Ti; The titanium alloy is prepared by a preparation method comprising the following steps: (1) Smelting titanium alloy raw materials, hot forging and hot rolling to obtain hot-rolled wire rods; (2) subjecting the hot-rolled wire rod to annealing heat treatment and pickling to obtain annealed hot-rolled wire rod; (3) subjecting the annealed hot-rolled wire rod to cold drawing deformation and low-temperature aging treatment to obtain the titanium alloy; The cross-sectional deformation of the cold drawing deformation is 30-40%; the temperature of the low-temperature aging treatment is 550-640° C., and the insulation time is 1-2 hours.

2. The titanium alloy according to claim 1, characterized in that In step (1), the hot forging temperature is 950-1250°C, the holding time is 1-2 hours, and the final forging temperature is not less than 900°C.

3. The titanium alloy according to claim 1, characterized in that: In step (1), the hot rolling temperature is 800-850°C, the holding time is 1-2 hours, and the final rolling temperature is not less than 750°C.

4. The titanium alloy according to claim 1, characterized in that In step (2), the annealing heat treatment temperature is 750-800° C., and the holding time is 1-2 hours.

5. Use of the titanium alloy according to any one of claims 1 to 4 in medical materials.

Citation Information

Patent Citations

  • Preparation method for high-fatigue property titanium alloy spring

    CN108838301A

  • High-strength antibacterial titanium alloy bar and wire and preparation method thereof

    CN112251639A